2010
DOI: 10.1111/j.1365-2982.2010.01492.x
|View full text |Cite
|
Sign up to set email alerts
|

Day-to-day reproducibility of prolonged ambulatory colonic manometry in healthy subjects

Abstract: Background-Although colonic manometry provides useful information regarding colonic physiology, considerable variability has been reported both for regional motility and manometric patterns. Whether colonic manometry is reproducible is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Gastrointestinal motility measurements are complicated by high variability in both humans and animal models. Here, we highlight three key points.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal motility measurements are complicated by high variability in both humans and animal models. Here, we highlight three key points.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, in 2010, Rao et al. investigated the day‐to‐day reproducibility of prolonged 24‐hour CM performed 2 weeks apart in healthy adults and demonstrated that the study findings were reproducible, particularly for the assessment of key physiologic changes, including HAPCs . In their study, colonic motility catheters were placed under minimal sedation unlike our own in which general anesthesia was used for catheter placement.…”
Section: Discussionmentioning
confidence: 94%
“…It may also be useful to examine the optimal time for treatment. Since there is a lack of waking patterns in colonic motility in patients with STC , TES in the morning may be more effective.…”
Section: Discussionmentioning
confidence: 99%